ANALISISSIKAP FAIR PLAYPADA PERMAINAN FUTSALSMA SE-KOTA BINJAI - Nurkadri, Nurkadri; Andriani, Rini; Munandar Hutagaol, Imam Aris (UNIVERSITAS NEGERI MAKASSAR, 2020)
This research is to find out how much is the understanding of the attitude of fair play in high school clubs in the city of Binjai. The research sample, namely the high school futsal club in the city of Binjai, among them are SMAN 1 Binjai, SMAN 2 Binjai, SMAN 4 Binjai, and SMAN 5 Binjai with 70 respondents. Data collection methods using questionnaire techniques that will be filled by respondents, the data were analyzed using descriptive analysis of percentages. Based on the results of the study note that the award for opposing players was 14.54%, cheating 5.3%, playing skills 9.3%, and respecting teammates 16.78%. It can be concluded that most of the futsal clubs in the city of Binjai are sufficient in understanding fair play. The researcher suggests to the school to pay more attention to improving the quality of coaching in futsal training in schools in giving a fair play attitude. The trainer must continue to improve teaching the understanding of fair play on an ongoing basis to their students. So that in the future an exciting and fun futsal game will be created,avoiding cheating and increasingly upholding the spirit of fair play.